Optimization of energy supply: 3d development for critical, wear-based insulatory components - Tkachuk, Ivan (Global Prosperity, 2025)
Abstract. The development of the energy sector, which is an indicator of successful economic development, requires the implementation of innovative advanced technological solutions. One such solution is 3D printing, which creates new opportunities for improving the energy equipment supply chain. The introduction of 3D printing not only reduces the financial and time resources required to manufacture critical and rapidly wearing insulation components, but also increases the flexibility and adaptability of production, allows for personalization of the process, and eliminates transportation constraints. Expanding the variety of materials and processes for 3D printing requires the development of industry standards for quality and certification. Other promising areas for improving the use of 3D printing in the energy equipment sector include attracting investment and establishing cooperation between stakeholders, actively using artificial intelligence and virtual reality, and optimizing institutional support.